Jonge kunstenaars uit het Antwerpse. - Kapel Campo Santo, Sint-Amandsberg; Gele Zaal Noordstarfonds, Gent; Museum Mevr. J. D'Hondt-Dhaenens, Deurle (Sint-Amandsberg : Cultureel Comité Sint-Amandsberg, 1983)
Bijl, Guillaume ; Bruneau ; Bruyninckx, Robert ; Debbaut, Charles ; Deckers, Jürgen V. ; Devos, Danny ; Ghekiere, Joris ; Hautman, Sigefride ; Jambers, Marc ; Luyten, Mark ; Morez, Paul ; Pacquée, Ria ; Schepers, Marc ; Stroobant, Dominique ; Tordoir, Narcisse ; Van Bergen, Thé ; Van Gestel, Fik ; Van Haevre, Johan ; Van Houten, Peter ; Van Kerkhoven, Annemie ; Van Ravels, Thérèse ; Van Soom, Luc ; Van Steen, Rob ; Verbist, Carlo ; Verelst, Patrick ; Verleye, Jan & Verbist, Luc ; Vertessen Liliane ; Wagemans, Frank ; Roelandt, Hugo ; Verlinden, Greet ; Holthof, Marc
Jonge kunstenaars uit het Antwerpse, Kapel Campo Santo, Sint-Amandsberg ; Gele Zaal Noordstarfonds, Gent ; Museum Mevr. J. D'Hondt-Dhaenens, Deurle, 17 september tot 23 oktober 1983
boek
Keywords: Antwerpen